2017
DOI: 10.1161/circimaging.116.005772
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography and Single-Photon Emission Computed Tomography Imaging in the Diagnosis of Cardiac Implantable Electronic Device Infection

Abstract: Both F-FDG PET-CT and LS yield high sensitivity, specificity, and accuracy, and thus seem to be useful for the diagnosis of CIED infection, based on robust data forF-FDG PET-CT but limited data for LS. When available,F-FDG PET-CT may be preferred.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(77 citation statements)
references
References 30 publications
0
73
0
4
Order By: Relevance
“…Fluoro-18-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET/CT) has been shown to be useful in early CIED infection and also differentiating between CIED infection and recent postimplant changes 17 18. In a systematic review by Juneau et al ,19 the pooled sensitivity of 18 F-FDG PET/CT for the diagnosis of CIED infection was 87% and pooled specificity was 94%. The use of 99m Tc-hexamethypropylene amine oxime-labelled autologous white blood cell ( 99m Tc-HMPAO-WBC) single-photon emission CT/CT (SPECT/CT) has also been examined in suspected CIED infections.…”
Section: Introductionmentioning
confidence: 99%
“…Fluoro-18-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET/CT) has been shown to be useful in early CIED infection and also differentiating between CIED infection and recent postimplant changes 17 18. In a systematic review by Juneau et al ,19 the pooled sensitivity of 18 F-FDG PET/CT for the diagnosis of CIED infection was 87% and pooled specificity was 94%. The use of 99m Tc-hexamethypropylene amine oxime-labelled autologous white blood cell ( 99m Tc-HMPAO-WBC) single-photon emission CT/CT (SPECT/CT) has also been examined in suspected CIED infections.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showed a sensitivity of 73%-100% and a specificity of 71%-100% for 18 F-FDG PET/CT in the diagnosis of infection in the pocket of a cardiac implantable electronic device (15). A second metaanalysis showed similar results, with a pooled sensitivity of 87% and specificity of 94% (16). For device-related or prosthetic endocarditis diagnosis, it has been shown that adding 18 F-FDG PET/CTpositive findings as a major criterion to the modified Duke criteria increased diagnosis sensitivity from 52%-70% to 91%-97% without compromising specificity (17,18).…”
Section: Functional Imaging Toolsmentioning
confidence: 90%
“…15,18,22,[26][27][28][29][30][31] However, one caveat is that the majority of studies evaluating diagnostic accuracy in suspected CIED-GPI only include confirmed cases or those with medium-to-high pre-test probability. Paradoxically, patients at the opposite end of the spectrum (with a lower pre-test probability of infection at initial presentation) are generally considered to pose a greater diagnostic challenge and by comparison are relatively underrepresented in these studies; arguably, a novel non-invasive diagnostic tool would be most useful in this group of patients, and further studies assessing the performance of 18 F-FDG in this group are desirable.…”
Section: Historical Perspectivementioning
confidence: 99%
“…Notably, studies of ventricular assist device (VAD) infection were also included in this analysis. 26 …”
Section: Historical Perspectivementioning
confidence: 99%